2019
DOI: 10.1039/c9nh00164f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient thermophones based on freestanding single-walled carbon nanotube films

Abstract: We present the state-of-the-art performance of air-coupled thermophones made of thin, freestanding films of randomly oriented single-walled carbon nanotubes (SWCNTs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Recently, the fusion of materials science and modern digital technologies, including robotics, cloud computing, and artificial intelligence (AI), has increasingly attracted researcher attention. Software-controlled chemical equipment is widely utilized in laboratories as powerful tools for the automated synthesis of target molecules 1,2 , polymers 3 , quantum dots (QDs) 4,5 , and 2-D materials 6 . These highthroughput automatic tools, which combined with in situ characterization methods, have significantly enhanced the efficiency and reproducibility of material synthesis.…”
mentioning
confidence: 99%
“…Recently, the fusion of materials science and modern digital technologies, including robotics, cloud computing, and artificial intelligence (AI), has increasingly attracted researcher attention. Software-controlled chemical equipment is widely utilized in laboratories as powerful tools for the automated synthesis of target molecules 1,2 , polymers 3 , quantum dots (QDs) 4,5 , and 2-D materials 6 . These highthroughput automatic tools, which combined with in situ characterization methods, have significantly enhanced the efficiency and reproducibility of material synthesis.…”
mentioning
confidence: 99%
“…However, it does not guarantee good reliable results, as was shown by Barnes et al, where an agreement with an experimental absorption spectrum was demonstrated only within 20%. 15 Besides, the AFM methods are not applicable in the case of freestanding films used in ultrasensitive photodetectors, 5 efficient ultrasound loudspeakers, 36 and extreme UV protective membranes, 37 which makes the preliminary thickness assessment a difficult (or even impossible) task. Another approach proposed by Kuwahara et al 38 is based on thick film optical constants applied as a reference for thin films.…”
mentioning
confidence: 99%
“…In Figure , normalized SPL (1 cm, 1W/cm 2 ) of different TA devices have been listed. ,,, Compared with other materials, graphene has the smallest thickness and an extremely low HCPUA of 5.8 × 10 –4 J × m –2 × K –1 , 1 order of magnitude smaller than monolayer CNT thin films. , Therefore, the normalized SPL of GTASS has the good performance. In 2011, Tian et al .…”
mentioning
confidence: 99%